Biodegradation of trichloroethylene (TCE) by methanotrophic community - Shukla A.K.; Vishwakarma P.; Upadhyay S.N.; Tripathi A.K.; Prasana H.C.; Dubey S.K. (My University, 2025)
Laboratory incubation experiments were carried out to assess the potential of methanotrophic culture for degrading TCE. Measurements of the growth rate and TCE degradation showed that the methanotrophs not only grew in presence of TCE but also degraded TCE. The rate of TCE degradation was found to be 0.19 ppm h-1. The reverse transcriptase-PCR test was conducted to quantify expression of pmoA and mmoX genes. RT-PCR revealed expression of pmoA gene only. This observation provides evidence that the pmoA gene was functionally active for pMMO enzyme during the study. The diversity of the methanotrophs involved in TCE degradation was assessed by PCR amplification, cloning, restriction fragment length polymorphism and phylogenetic analysis of pmoA genes. Results suggested the occurrence of nine different phylotypes belonging to Type II methanotrophs in the enriched cultures. Out of the nine, five clustered with, genera Methylocystis and rest got clustered in to a separate group. © 2008 Elsevier Ltd. All rights reserved.